Injury-related hospitalisation in community-dwelling older people across the cognitive spectrum: A population based study. (July 2019) - Harvey, L.A.; Toson, B.; Brodaty, H.; Draper, B.; Kochan, N.; Sachdev, P.; Mitchell, R.; Close, J.C.T.
Highlights: We compared injury hospitalisation rates for people across the cognitive spectrum. People with MCI had higher injury rates than people with normal cognition. People with MCI had lower injury rates than people with dementia. Upper limb fractures were most common injury for people with normal cognition. Non-fracture head injuries were most common injury for people with MCI and dementia. Abstract: Objectives: To describe the injury profile, hospitalisation rates and health outcomes for older people with cognitive impairment and to determine whether these differ from those with normal cognition. Methods: Participants were 867 community-dwelling 70–90 year olds enrolled in the population-based longitudinal Sydney Memory and Ageing Study (MAS). Participant's cognitive status was classified as normal, mild cognitive impairment (MCI) and dementia at baseline, then 2, 4 and 6 years' follow-up. MAS records were linked to hospital and death records to identify injury-related hospitalisations for the 2-year period following each assessment. Results: There were 335 injury-related hospitalisations for participants; 222 (25.6%) participants had at least one injury-related hospitalisation. The injury-related hospitalisation rate for participants with MCI (63.0 [95%CI 51.6–74.4] per 1000 person-years) was higher than for people with normal cognition (39.3 [95%CI 32.4–46.1] per 1000 person-years) but lower than people with dementia (137.1 [95%CI 87.2–186.9] per 1000 person-years). Upper limb fractures (22.1%) were the most common injuries for participants with normal cognition, and non-fracture head injuries for participants with MCI and dementia (25.9% and 23.3% respectively). Participants with dementia had a higher proportion of hip fractures (20.0%, p = 0.0483) than participants with normal cognition. There was no difference in 30-day mortality between participants with normal cognition, MCI and dementia (3.9%, 1.7%, 3.3% respectively). Conclusion: Older people with objectively defined MCI are at higher risk of injury-related hospitalisation than their cognitively intact peers, but lower risk than people with dementia. Falls-risk screening and fall prevention initiatives may be indicated for older people with MCI.